2022
DOI: 10.3329/jafmc.v17i1.56714
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Barotrauma in Military Aircrew: Analysis of Risk Factors

Abstract: Introduction: Middle ear barotrauma is a common medical problem related to aviation; because the aviation environment exposes the aviator to a rapidly changing ambient pressure. Middle ear barotrauma occurs when the Eustachian tube failed to equalize middle ear pressure with ambient pressure during flight. Objective: To determine the prevalence of middle ear barotraumas among aircrew on Bangladesh Air Force (BAF) and to find the risk factors of middle ear barotrauma. Materials and Methods: This cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
1
Order By: Relevance
“… 7 The literature review of middle ear barotrauma done in military aircrews showed the prevalence of 12% which is slightly lower than our study on para-pilots. 8 A study done in aircraft passengers revealed the prevalence of 14% which is slightly higher than our survey. 9 …”
Section: Discussioncontrasting
confidence: 72%
“… 7 The literature review of middle ear barotrauma done in military aircrews showed the prevalence of 12% which is slightly lower than our study on para-pilots. 8 A study done in aircraft passengers revealed the prevalence of 14% which is slightly higher than our survey. 9 …”
Section: Discussioncontrasting
confidence: 72%
“…Pada derajat 4, perdarahan telah terjadi pada telinga bagian dalam. Pada derajat 5, selain tampak adanya perdarahan pada liang telinga luar, derajat ini disertai juga dengan ruptur membran timpani (Liton et al, 2022;Nofz et al, 2020). Dari 33 responden yang mengalami barotrauma telinga tengah dan dalam, teridentifikasi dalam penelitian ini sebanyak 27 orang (81,8%) diantaranya sudah masuk dalam derajat 1, terdapat 5 orang (15,2%) dengan derajat 2 dan 1 orang (3%) dengan derajat 3.…”
Section: Karakteristik Barotrauma Telingaunclassified